SOME IMPLICATIONS OF THE USE OF COMPUTERS IN INDUSTRY. - Hurni, M. L. (The Accounting Review, 1954)
The article presents a study on implications of the use of computers in industry. Well-informed, forward thinking individuals have identified the possibility that routine sensing and judgment work now performed by people will be taken to an important degree by machines. These observations are based upon two developments. First is the development of methods for reducing complex problems to terms that the human mind can grasp and understand in their entirety. Second is the availability of the aforementioned computers for use as research tools for processing the masses of data that may have to be examined in the course of reducing the complex problem to its simpler form. The method is based upon the premise that many of businesses have sufficient maturity for stable operational patterns to have evolved. The ultimate expectation is that these principles can be quantitized and expressed mathematically. When this end is attained, it should then be possible for a computational machine to take over and, operating in accordance with the desired mathematical expression, sense deviations and indicate or even take action.